2010
DOI: 10.1089/ten.tea.2009.0307
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell–Related Gene Expression in Clonal Populations of Mesenchymal Stromal Cells from Bone Marrow

Abstract: Decline in the frequency of potent mesenchymal stem cells (MSCs) has been implicated in ageing and degenerative diseases. Increasing the circulating stem cell population can lead to renewed recruitment of these potent cells at sites of damage. Therefore, identifying the ideal cells for ex vivo expansion will form a major pursuit of clinical applications. This study is a follow-up of previous work that demonstrated the occurrence of fast-growing multipotential cells from the bone marrow samples. To investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 62 publications
3
22
0
Order By: Relevance
“…Certainly, there is great divergence in transcriptional signature between high-and lowpotential clones following exposure to differentiation conditions (Mareddy et al, 2010). There is also now evidence for clonal variation in basal gene expression in undifferentiated cells.…”
Section: Inter-clonal Molecular Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, there is great divergence in transcriptional signature between high-and lowpotential clones following exposure to differentiation conditions (Mareddy et al, 2010). There is also now evidence for clonal variation in basal gene expression in undifferentiated cells.…”
Section: Inter-clonal Molecular Variationmentioning
confidence: 99%
“…There is also now evidence for clonal variation in basal gene expression in undifferentiated cells. Screens comparing stem cell gene expression between fast-and slowgrowing clones identify extensive differences in the expression of genes associated with the cell cycle and cellular division (Mareddy et al, 2010;Menicanin et al, 2010). Fast-growing clones also express select growth factors (e.g.…”
Section: Inter-clonal Molecular Variationmentioning
confidence: 99%
“…[1][2][3][4][5] A recent study showed that MSCs can be expanded for more than 50 passages in cell culure. 6 MSCs have a fibroblast-like morphology and express stromal markers, including CD73, CD105, CD29, CD44, and CD90, but not hematopoietic markers.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, ADAM12 expression is also up-regulated in mesenchymal stem cells (11), neural stem cells (12), stem cells of the spleen (13), and stem cells of the liver (14). Each of these stem cell types is associated with high levels of Notch activity (13)(14)(15)(16)(17)(18). Furthermore, ADAM12 is expressed in regenerating skeletal muscle (19,20).…”
mentioning
confidence: 99%